Optical coherence tomography (OCT) in central retinal occlusion with sparing cilioretinal artery – a case report - Mańkowski, Wojciech; Wylęgała, Edward (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The authors present a case of central retinal artery occlusion with sparing cilioretinal artery in 62 years old woman with sudden decrease of visual field in the right eye. The diagnosis of central retinal artery occlusion (ophthalmological examination, fluorescein angiography, field of vision and optical coherent tomography) was performed at the begining and after 1 month. In acute phase, optical coherence tomography reveals increased thickness and reflectivity of the inner retinal layer and decreased reflectivity of the outer retinal layer. After one, three and six months OCT demonstrates a decrease of reflectivity and thickness of the inner retina and increase of reflectivity of the outer layer. Spectral OCT performed after six months from the beginnig of the disease shows atrophy of the retinal neurosensory layer.